Determinants of Microfinance Institutions’ Financial Performance in Indonesia - Yahya Riantas; Mokhamad Anwar; Sutisna (Universitas Negeri Semarang, 2025)
This study investigates the determinants of financial performance in Indonesian Microfinance Institutions (MFIs), analyzing financial and social factors alongside the impacts of COVID-19. Using panel data from 242 OJK-regulated MFIs from 2018 to 2023 (1,452 observations), fixed-effects regression reveals that the Debt-to-Equity Ratio (DER), Women’s Empowerment Index (WEI), and Microcredit Proportion (PMC) negatively affect Return on Assets (ROA), while Firm Size (SIZE) and Loan-to-Deposit Ratio (LDR) show positive effects. Service Accessibility (ACCES) proves to be insignificant. The findings highlight a critical trade-off: while MFIs’ social missions such as women’s empowerment and microcredit expansion depress profitability, operational scale and liquidity management enhance performance. The pandemic exacerbated these tensions, particularly in under-supported empowerment programs. This study contributes to the microfinance literature by empirically validating capital structure and social performance theories in Indonesia’s unique context. Practical implications suggest optimizing capital structures to reduce leverage risks, balancing microcredit portfolios with larger loans, and integrating digital tools to improve efficiency. For policymakers, these insights underscore the need for regulations harmonizing financial sustainability with inclusive development goals. By bridging empirical gaps, this research offers a framework for MFIs navigating post-pandemic recovery while maintaining their dual social–financial mission.